IMPLEMENTASI TEKNOLOGI AUGMENTED REALITY DALAM PENYAJIAN MENU DI OUTLET STARMILKSHAKE - Nazrie, Nazrie Abdul Fikri; Dasa Putri, Anggia (LPPM Universitas Putera Batam, 2022)
The only way to view the menus at beverage establishments is on paper, which is displayed by the waiter who displays the menu names in text along with the cost of a drink. This menu paper model is thought to be less attractive and less effective. However, with menu applications using augmented reality technology, customers can find detailed menu information about menus at beverage establishments in the form of attractive 3D objects. The approach taken in this instance